Kinetic of Hexavalent Chromium (Cr(VI)) Removal by Corn Cob-Based Activated Carbon Modified with Nitric Acid - Ratnaningsih, Wahyu; Aningtyas, Vebri; Shabrina, Husna Muizzati; Arifin, Uma Fadzilia; Prayogo, Wisnu; Amin, Muhammad (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
The presence of heavy metal Cr(VI) in water indicates environmental pollution. Heavy metal Cr(VI) that exceeds the standard can be harmful to health because it is toxic and carcinogenic. Activated carbon can be used as a heavy metal adsorbent. Modification of activated carbon using nitric acid can increase metal adsorption capacity. Therefore, this study aims to determine the kinetic of hexavalent chromium (Cr(VI)) removal by corn cob-based activated carbon modified with nitric acid. The modified activated carbon was characterized by Boehm titration and FTIR spectrophotometer. The adsorption capacity was identified in various parameters, involving the initial concentration of Cr(VI), pH value, contact time, and concentration of the adsorbent to obtain the optimal Cr(VI) removal efficiency value. The most optimal Cr(VI) adsorption was obtained at an activated carbon dosage of 3 g/L, pH value of 1, contact time of 140 minutes, and 100 mg/l Cr(VI) concentration. Based on adsorption kinetics data, the pseudo-second-order equation was obtained (R2 =0.994). The adsorption phenomenon followed the Langmuir isotherm model (R2 = 0.998) with an optimum adsorption capacity of 28.32 mg/g. Corn cob-activated carbon modified with nitric acid has many acidic groups that act as effective active sites for reducing Cr(VI) from water.